Perspektif Adil Gender Dalam Aturan Tata Tertib Mahasiswa IAIN Antasari Banjarmasin - Jamal Syarif (An Nisa'a, 2017)
Women who have the right to equal rights with men are regarded as individual beings who can only take care of domestic affairs. In the reality of reality in the society of many women who have been active in the public world, they are still regarded as individuals who also have to take care of domestic affairs. Moving on from the issue, issues of gender inequality in laws, regulations, and policies, the researcher is interested to examine more deeply about IAIN Antasari Rector Decree on IAIN Antasari Banjarmasin Student Rules Act. The review of the regulation is focused on chapters, chapters and verses that have relevance to the issue of gender relations and the empirical problems that may exist in IAIN Antasari Banjarmasin.